On Experimental Energy Consumption Estimation of a 6-DoF Industrial UR3e Robot Arm Manipulator in Trajectory Planning - Hosseini, Sara; Hahn, Ingo (IEEE International Workshop on Robot and Human Communication, RO-MAN, 2024)
This paper proposes an energy consumption estimation in the trajectory planning task of an industrial robot (IR) arm manipulator. Human-robot collaborative scheduling has become integral to modern manufacturing. Effective scheduling of human-robot cooperation is crucial for enhancing production efficiency. However, energy-efficient trajectory planning in human-robot interaction remains an unexplored area. To address this, a 6-DoF (Degree of Freedom) robot arm, available in the laboratory, was utilized to assess the energy consumption of this specific robot type. However, his approach can be applied to any robot, whether it's a human-robot collaboration, a mobile robot, or any other articulated robot arm manipulator.For this goal the electrical and mechanical losses of a 6-DoF robot arm manipulator from the company Universal Robots is modeled and its power losses cost function (PLCF) is derived correspondingly to calculate the electromechanical energy losses. The objective of this paper is to estimate the energy losses in a trajectory planning task in cartesian space for a tool center point (TCP) of the robot, starting from an initial point and resting at a final point. This goal is achieved by examining and analyzing the kinematics and dynamics followed by measuring the velocity and acceleration related terms of each motor at each joint of the UR3e robot arm in a laboratory setup. The results estimate the changes of energy losses in the overall trajectory following of the robot manipulator and presents the results of the estimated and measured reduction terms.
CRIS-Team Scopus Importer:2024-11-29
Keywords: electromechanical losses; industrial robot; motion planning; power consumption; six degree of freedom robot